2023
DOI: 10.1155/2023/6603522
|View full text |Cite
|
Sign up to set email alerts
|

Rhinacanthin C Ameliorates Insulin Resistance and Lipid Accumulation in NAFLD Mice via the AMPK/SIRT1 and SREBP‐1c/FAS/ACC Signaling Pathways

Abstract: Rhinacanthin C (RC) is a naphthoquinone ester with an anti-inflammatory activity extracted from Rhinacanthus nasutus (L.) Kurz (Rn). It has been proven to improve hyperglycemia and hyperlipidemia, but the prevention and mechanism of RC in nonalcoholic fatty liver disease (NAFLD) are not clear. In the current study, we first extracted RC from Rn using ethyl acetate and identified it by HPLC, MS, and NMR. At the same time, molecular docking analysis of RC with AMPK and SREBP-1c was performed using AutoDock softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…SREBP-1c mainly regulates genes related to triglyceride and fatty acid synthesis, such as ACC and SCD1 [49]. Recent studies have shown that SREBP-1c can also inhibit the transcription of insulin receptor substrate-2 (IRS-2), thereby exacerbating insulin resistance; this suggested that it might have a negative regulatory effect on insulin signaling [50,51]. ChREBPα is a transcription factor in the glucose signaling pathway, which plays an important role in regulating glucose metabolism [52], fat metabolism, and fat deposition in mammals [53].…”
Section: Discussionmentioning
confidence: 99%
“…SREBP-1c mainly regulates genes related to triglyceride and fatty acid synthesis, such as ACC and SCD1 [49]. Recent studies have shown that SREBP-1c can also inhibit the transcription of insulin receptor substrate-2 (IRS-2), thereby exacerbating insulin resistance; this suggested that it might have a negative regulatory effect on insulin signaling [50,51]. ChREBPα is a transcription factor in the glucose signaling pathway, which plays an important role in regulating glucose metabolism [52], fat metabolism, and fat deposition in mammals [53].…”
Section: Discussionmentioning
confidence: 99%
“…Rhinacanthin decreases adipogenic marker expression, including that of PPARγ, C/EBPα, and aP2, by phosphorylating AMPKα. Moreover, it suppresses adipogenesis by deactivating SREBP-1c, acetyl-CoA carboxylase, Fas cell surface death receptor, and stearoyl-Coenzyme A desaturase 1 [ 40 ]. AMPKα activation is widely recognized to inhibit C/EBPα, C/EBPβ, and PPARγ expression during adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-α has been demonstrated to be involved in fatty acid metabolism in various tissues, including the liver, and the activation of PPAR-α leads to significant improvements in hepatic steatosis and inflammation in NAFLD [66]. SREBP-1c can increase the expression levels of lipogenic genes such as FAS and ACC, which enhances the synthesis of fatty acids and accelerates the accumulation of TG [67]. The upregulation of SREBP-1c, along with its downstream genes including FAS and ACC, as well as the downregulation of PPAR-α, are recognized as the interfering factors contributing to the development of hepatic steatosis [68].…”
Section: Discussionmentioning
confidence: 99%